Chile and its Potential Role Among the Most Affordable Green Hydrogen Producers in the World - Acosta, Kevin; Salazar, Iván; Saldaña, Manuel; Ramos, Jahir; Navarra, Alessandro; Toro, Norman (Frontiers in Environmental Science, 2022)
As result of the adverse effects caused by climate change, the nations have decided to accelerate the transition of the energy matrix through the use of non-conventional sources free of polluting emissions. One of these alternatives is green hydrogen. In this context, Chile stands out for the exceptional climate that makes it a country with a lot of renewable resources. Such availability of resources gives the nation clear advantages for hydrogen production, strong gusts of wind throughout the country, the most increased solar radiation in the world, lower cost of production of electrical supplies, among others. Due to this, the nation would be between the lowest estimated cost for hydrogen production, i.e., 1.5 USD/kg H2 approximately, scenario that would place it as one of the cheapest green hydrogen producer in the world.